Pleural Effusion in Gorham-Stout Syndrome: A Case Report and a Literature Review - Alberto, Valsecchi; Sabrina, Arondi; Giampietro, Marchetti (Cancers Review, 2015)
Gorham-Stout syndrome (GSS) is an uncommon disease characterized by massive osteolysis due to bone resorption associated with proliferation of blood or lymphatic vessels. Pleural effusion is an uncommon manifestation. We present a case report of GSS in a 46 year old patient admitted for bilateral serohematic pleural effusion and a review of the literature regarding GSS associated with pleural effusion. We analyzed 48 clinical casesfounded in English language literature concerning pleural effusion secondary to GSS. Patients affected by GSS manifesting pleural effusion are prevalently male with a large range of age. Pleural effusion is more frequently chylous (86%), but it can be also serohematic, transudative or bloody. Direct pleural involvement by the disease has been assessed only in some cases of chylothorax, otherwise the pathological process underlying the liquid production remains unknown. Pleural effusion is most of time bilateral. More frequently it conditions ingravescent dyspnea and when it is chylous it can determine malnutrition. No standard therapy has been established. In patients with relapsing pleural effusion several therapeutic approaches have been used: radiation therapy on mediastinum, pleurodesis, thoracic duct ligation, octreotide administration. Radiation therapy seems to be effective even when applied only on the bone lesions. Bisphosphonates and alpha-2b Interferon are useful to improve the multiple sites of disease, thanks to their systemic action. The papers considered report a short follow up time, during which almost 50% of the treated patients had no recurrences, but more or less 20% of the patients died.